PATHOMORPHISM OF INFILTRATIVE PULMONARY TUBERCULOSIS FOR A 20-YEAR PERIOD - A. A. Chushkina; N. M. Koretskaya (Acta Biomedica Scientifica, 2012)
Pattern of age, sex and social composition of newly diagnosed patients with infiltrative pulmonary tuberculosis was studied as well as characteristic features of the developed particular process and its clinical manifestations in three phases, covering a 20-year period, of observation (1989 - 105 patients, 2004 - 161 patients, 2009 - 399 patients). It was found that for 20 years infiltrative tuberculosis was subjected to significant pathomorphism which showed an increase in the proportion of cases among persons of older age groups and. women, an increasing role of exogenous superinfection and. concomitant diseases of the risk group in its pathogenesis, growth of damage at a constant rate of destruction and. bacterioexcretion. It is stated that in the dynamics there is an increase in frequency of primary drug resistance in tuberculosis Mycobacterium and. the loading of its structure. The features of clinical and. laboratory manifestations of infiltrative pulmonary tuberculosis are distinguished in modern conditions.